Criteria for the objectivity of epidemiological studies of exposure environmental factors on the health of the population - Talykova L.V.; Bykov V.R. (Российская Арктика)
The article presents the experience of conducting large-scale epidemiological studies of the mortality parameters of the population of single-industry towns of the Murmansk region, where the workshops of the leading cityforming enterprises for the extraction and processing of apatite-nepheline and sulfide copper-nickel ores are concentrated. The maximum mortality rate from oncological diseases among workers of apatite production has been established. The probable role of natural radioactive elements in cancer mortality is considered. The main materials and methods of forming the first full-fledged birth register in the Russian Federation are described, which served as a unique tool for joint epidemiological studies with Norwegian specialists on the relationship between occupational exposure and reproductive disorders in women engaged in nickel production. In addition to the level of professional exposure to nickel, the register made it possible to assess the role of other industrial and social factors in the formation of reproductive health disorders. The difficulties in organizing such studies at the present time, including those determined by a number of legislative acts, are formulated.